The relationship between language proficiency and Iranian EFL learners' knowledge of vocabulary depth versus vocabulary breadth - Gholam-Ali Tahmasebi; Hamidreza Haghverdi; Mehdi Ghaedrahmat (Universidad de La Sabana, 2013)
The present study intended to examine the relationship between language proficiency and Iranian EFL learners' knowledge of vocabulary depth versus vocabulary breadth. To achieve this end, 80 students at Upper and Lower-Intermediate levels were randomly chosen from the population of Shahid Beheshti School in Khoramabad as participants of this study. First of all, an Oxford Placement test (OPT) was administered to determine the subjects' level of proficiency. Each group at upper- and lower-intermediate levels received Nation 2000, 3000, and 5000 tests to determine the vocabulary size of the learners. Two weeks later, Vocabulary Knowledge Scale (VKS) was used in order to determine the learners' vocabulary depth. The results of the correlation coefficients indicated that there was a significant relationship between vocabulary breadth, vocabulary depth and language proficiency of the learners. In addition, the results of multiple regression revealed that vocabulary depth is a better predictor of learners' language proficiency than of vocabulary breadth. Keywords: language proficiency, vocabulary breadth, vocabulary depth, EFL learners, vocabulary knowledge scale.